Fostering the post-development debate: the Latin American concept of tecnologia social - Pozzebon, Marlei; Fontenelle, Isleide Arruda (Third World Quarterly, 2018)
This essay revisits the historical development of a concept – tecnologia social – as one avenue for discussing alternatives to post-development, arguing that the Western-based historical path of technology development is one of the main sources of growing human impoverishment, social inequalities and economic dependency. The concept of tecnologia social points towards political processes that create opportunities to redefine the arrangements among social groups, artefacts and methods used in everyday life, particularly for production and consumption. Because the post-development debate has been criticised for formulating a sound and strong critique to mainstream development but failing to propose concrete empirical alternatives, we seek to foster the debate through the Latin American concept of tecnologia social.
Keywords: Amérique latine; Libre accès; Social technology; Technologie sociale

Fostering the post-development debate: the Latin American concept of tecnologia social - Pozzebon, Marlei; Fontenelle, Isleide Arruda (Third World Quarterly, 2018)
This essay revisits the historical development of a concept – tecnologia social – as one avenue for discussing alternatives to post-development, arguing that the Western-based historical path of technology development is one of the main sources of growing human impoverishment, social inequalities and economic dependency. The concept of tecnologia social points towards political processes that create opportunities to redefine the arrangements among social groups, artefacts and methods used in everyday life, particularly for production and consumption. Because the post-development debate has been criticised for formulating a sound and strong critique to mainstream development but failing to propose concrete empirical alternatives, we seek to foster the debate through the Latin American concept of tecnologia social.
Keywords: Amérique latine; Libre accès; Social technology; Technologie sociale

Fostering the post-development debate: the Latin American concept of tecnologia social - Pozzebon, Marlei; Fontenelle, Isleide Arruda (Third World Quarterly, 2018)
This essay revisits the historical development of a concept – tecnologia social – as one avenue for discussing alternatives to post-development, arguing that the Western-based historical path of technology development is one of the main sources of growing human impoverishment, social inequalities and economic dependency. The concept of tecnologia social points towards political processes that create opportunities to redefine the arrangements among social groups, artefacts and methods used in everyday life, particularly for production and consumption. Because the post-development debate has been criticised for formulating a sound and strong critique to mainstream development but failing to propose concrete empirical alternatives, we seek to foster the debate through the Latin American concept of tecnologia social.
Keywords: Amérique latine; Appropriation technologique; Social technology; Technologie sociale